The future of the oceans past: towards a global marine historical research initiative - HOLM, POUL (My University, 2014)
Historical research is playing an increasingly important role in marine sciences. Historical data are also used in policy making and marine resource management, and have helped to address the issue of shifting baselines for numerous species and ecosystems. Although many important research questions still remain unanswered, tremendous developments in conceptual and methodological approaches are expected to contribute to a comprehensive understanding of the global history of human interactions with life in the seas. Based on our experiences and knowledge from the ‘‘History of Marine Animal Populations’’ project, this paper identifies the emerging research topics for future historical marine research. It elaborates on concepts and tools which are expected to play a major role in answering these questions, and identifies geographical regions which deserve future attention from marine environmental historians and historical ecologists.
PUBLISHED
https://www.academia.edu/7585828/The_Future_of_Oceans_Past_Towards_a_Global_Marine_Historical_Research_Initiative
Keywords: Marine history; Identities in Transformation; Smart & Sustainable Planet